HUBUNGAN MOTIVASI, PERSEPSI MELALUI STRATEGI PEMBELAJARAN TERHADAP PRESTASI BELAJAR BAHASA INDONESIA SISWA KELAS IX SMP NEGERI 1 PAGAR ALAM - Erly Purnawan (UNIB Press, 2022)
This study aims to analyze the correlation among motivation, perception towards learning strategy and indonesian learning achievement of the ninthgrade students of SMP Negeri 1 Pagar Alam. This research is a quantitative study with a correlational method. The population in this study were all the ninthgrade students of SMP Negeri 1 Pagar Alam in the academic year 2020-2021. The sampling technique used in this study was purposive sampling technique. The research instrument was a motivation questionnaire, a perception questionnaire through learning strategies and documentation of student achievement in odd semesters. The data analysis technique used to test the correlation between variables X1 to Y and X2 to Y is r-product moment correlation analysis, to test the correlation of Xi, X2 to Y, multiple regression analysis is used. The results showed that there was a significant relationship between motivation and perception through learning strategies simultaneously on learning achievement in Indonesian. A significance score of 0.001 is lower than 0.05